Enhancing target detection capability of the vessel traffic service (VTS) system on the Cai Mep - Thi Vai channel - Minh Tri, Truong; Gia Huy, Dinh (Journal of Transportation Science and Technology, 2024)
This study addresses the limitations of the current Vessel Traffic Service (VTS) system in monitoring and ensuring navigational safety on the Cai Mep-Thi Vai channel, a crucial waterway in Vietnam's maritime transport system. This research aims to propose solutions to improve the target detection capability of the VTS system in this area. Through surveys and analysis of the current status, this study identifies the system's shortcomings and proposes solutions such as installing additional radar stations and cameras. The proposed solution offers a systematic approach to enhance the effectiveness of the VTS system in managing and monitoring maritime traffic on the Cai Mep-Thi Vai channel, thereby contributing to navigational safety and security. This study provides feasible solutions that can be implemented in practice to address the limitations of the current VTS system.
Keywords: Vessel Traffic Service (VTS); Target detection; Cai Mep - Thi Vai channel; Radar station